Diabetes Detection and Prevention in Dermatology - Ngo, Alexandra; Froessl, Luise; McWhorter, John Wesley; Perkison, William Brett; Katta, Rajani (Dermatology Practical & Conceptual, 2021)
We are currently in the midst of an international epidemic of diabetes mellitus (DM) and prediabetes. The prevalence of DM in the United States is estimated at 9.4% of the population across all ages, while an estimated 1 in 3 Americans (33.9%) has prediabetes. According to the WHO, about 60 million people suffer from diabetes in the European Region. Dermatologists may play an important role in tackling this epidemic via efforts to improve early detection of both diabetes and prediabetes. Dermatologists often treat patients with, or at risk of, diabetes. This includes patients who present with cutaneous manifestations such as acanthosis nigricans, as well as patient populations at increased risk, including those with psoriasis, hidradenitis suppurativa, and polycystic ovarian syndrome. Simple screening guidelines can be used to identify patients at risk, and screening can be performed via a single non-fasting blood test. The diagnosis of prediabetes is a key feature in diabetes prevention, as interventions in this group can markedly reduce progression towards diabetes. In addition to referral to a primary care physician, dermatologists may refer these patients directly to structured behavioral lifestyle intervention programs known as diabetes prevention programs. A significant portion of the population lacks routine care by a primary care physician, and current data indicates need for improvement in diabetes screening and prevention among patient groups such as those with psoriasis. These factors highlight the importance of the dermatologist’s role in the detection and prevention of diabetes.